2014
DOI: 10.1111/jdv.12758
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical tacrolimus for oral lichen planus: real‐life experience in a retrospective cohort of patients with a review of the literature

Abstract: This retrospective analysis confirms that topical tacrolimus is a valuable therapeutic option in severe or treatment-resistant OLP. Our findings in daily practice suggested nevertheless that the efficacy of topical tacrolimus is overestimated with regard to both complete response and pain reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
1
18
1
1
Order By: Relevance
“…There have been safety concerns also related to TAC use in OLP, as a few case reports describe oral squamous cell carcinoma (SCC) developing after use of topical TAC (Becker et al , ; Mattsson et al , ; Morita et al , ). Although at the moment no firm evidence links topical TAC to oral SCC (Lopez‐Jornet et al , ; Ribero et al , ), it seems advisable that TAC is used for short periods only in cases not responsive to topical corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…There have been safety concerns also related to TAC use in OLP, as a few case reports describe oral squamous cell carcinoma (SCC) developing after use of topical TAC (Becker et al , ; Mattsson et al , ; Morita et al , ). Although at the moment no firm evidence links topical TAC to oral SCC (Lopez‐Jornet et al , ; Ribero et al , ), it seems advisable that TAC is used for short periods only in cases not responsive to topical corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, topical tacrolimus therapy improved lesions in 15 of 16 women with vulvar lichen planus [16]. Nevertheless, in one study, only 7 patients of 21 who were diagnosed with oral lichen planus and treated with topical 0.1% tacrolimus twice daily showed complete response at month 6; although it was a retrospective study, the authors suggested that the efficacy of topical tacrolimus was overestimated in daily practice [17]. Al-Mutairi et al reported 13 patients with lichen planus pigmentosus who were treated with tacrolimus ointment and 7 (53.8%) of them showed prominent lightening of the pigmentation within 12 weeks [18].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the retrospective analysis conducted by Ribero et al, only 20% of patients achieved complete remission at 2 months, and 33% achieved remission after a 6month treatment with tacrolimus [45]. The average duration of tacrolimus treatment is 2 months, with four applications per day.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 91%
“…Guo et al reported no adverse effects, while Resende et al described mild and transient side effects [43,44]. Ribero et al also found that patients reported a transitory burning sensation and altered taste sensation [45].…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%